A Citizen-Based Platform Reveals the Distribution of Functional Groups Inside a Large City from the Southern Hemisphere: E-Bird and the Urban Birds of Santiago (Central Chile) - Castro-Morales, S; Azocar-Guzman, M; Azocar-Guzman, M; Gutierrez-Tapia, P (BioMed Central Ltd., 2018)
Background: Current knowledge of urban bird ecology and biodiversity relies on evidence from cities of the Northern Hemisphere, while the Southern Hemisphere is underrepresented. Santiago is a large city from South America, located in central Chile, which is both a biodiversity hotspot and an Endemic Bird Area. This work is a synthesis, which aims to provide a diversity account for Santiago, and to describe the broad geographic distribution and bird functional patterns. Methods: We synthesized a seven-year (2009-2016) bird register from the eBird database (21,865 georeferenced registers at Santiago) into a single avifaunal account, along with the observed number of individuals. We complemented these registers by using available literature about Santiago s avifauna (28 references). We investigated the proportion of native/ exotic, migrants/residents, conservation categories, and urban nesting status. We classified Santiago s birds into seven trophic guilds. We plotted species richness and number of individuals for each functional group, by interpolating trough the Inverse Distance Weighted Method. Results: We found that Santiago s avifauna (46 species) is composed mainly by native (41), resident (38), non-threatened species (46) that breed inside the city (31). Some functional groups inhabit a large portion of Santiago s urban surface, reaching high values of richness and abundance. Among these groups are the native, urban-nesters and resident species; even though exotics possess low species richness (5), they are abundant and inhabit the complete urban surface of the city. The dominant trophic guilds are omnivorous (11) and granivorous (10). Insectivorous are the third most abundant trophic guild, and show the highest species richness (13). Conclusion: The functional groups with lower species richness are less abundant and display reduced and patchy distributions in Santiago. This is probably because of the low availability of suitable habitats and/or restricted food supply (migrants, carnivorous, nectarivorous, frugivorous, herbivorous and piscivorous). The high insectivorous richness reported in Santiago, along with similar patterns reported in several cities in the Neotropics, provides evidence to postulate a pattern of high species richness of this guild in cities across this biogeographic realm. © The Author(s).